(untitled) (International Journal of Physiotherapy, 2015)
Background: Students tends to develop poor posture as their work requires prolong sitting, such as in taking lectures, working on computer, lab activities, assignments using laptops etc. Sitting for prolong periods of time in front of computer resulting in various types of muscular pain which are due to in appropriate computer ergonomics and poor body posture. The objective of the study is to evaluate the awareness of good working posture and computer ergonomics among medical students of isra university, Hyderabad. Methods: A cross sectional study has done on 100 medical students of Isra University Hyderabad. Study was convenient and self-structured questionnaire used. Data analysis was done by using statistical package for social sciences (SPSS) 14 version Results: Questionnaires of 100 participants were completed and returned back for analysis (response rate of 100%). 80% students said they are aware of good posture and computer ergonomics but only 34% selected the right answer regarding good posture.66% students are habitual to use support while using computer, especially back support and ergonomic chair only.55% students said they never had their posture assessed. Conclusion: This study reveals that majority of students clamed to aware of good posture but their answerers has shown that there is lack of knowledge regarding good posture. Students are habitual to use support while sitting which is limited to use of back support and chair and still they need to know the principles of computer ergonomics regarding screen, mouse, keyboard, and overall work station.